OPTIMALISASI PEMBELAJARAN BERBASIS DIGITAL MELALUI APLIKASI SEBAGAI MEDIA PENUNJANG TUGAS AKADEMIK DAN KREATIVITAS SISWA DI SMPN 27 DEPOK - Adi Kurnia Sena; Hadi Zakaria; Allifiah Firnando; Fachriza Khairul Fajri; Farsya Runa Supriyatna; Ilham Bustomi; Lisa Ardeliana; Putra Bagus Satrio; Rara Anggraeni; Fahri Patir Ramadhan; Reza Putra Nurhudaya (Abdi Jurnal Publikasi, 2025)
This study aims to improve digital literacy and the ability to utilize artificial intelligence (AI) technology among junior high school students as an effort to prepare them for developments in digital-era education. The method used in this research is the implementation of an application-based platform that functions as a digital learning medium to help students understand AI concepts and apply them in completing academic tasks as well as developing creativity. The use of AI in learning is an essential aspect of modern education systems. However, AI concepts and technologies are often difficult to understand for junior high school students who are still at the early stages of digital literacy. Therefore, this study seeks to present a learning approach that is easy to understand, safe to use, and relevant to students’ academic needs, Through Navigator AI, students are introduced to various tools such as summarization, creative idea development, and AI-based educational content creation. This approach is expected to enhance students’ understanding of using technology productively, creatively, and ethically. The results of this study are expected to contribute to improving the quality of digital learning in junior high schools, particularly in utilizing artificial intelligence technologies. In addition, this research is expected to serve as a reference for teachers in developing innovative, interactive, and adaptive teaching methods aligned with digital technology advancements in primary and secondary education.